Caracterização imunoquímica e molecular da fração dermonecrótica do veneno da aranha marrom Loxosceles intermedia - Juliana Ferreira de Moura (2005)
To investigate the biochemistry and the immunochemistry of proteins from L. intermedia spider venom, thirteen monoclonal antibodies were produced. On of them,called LimAb7, was able to neutralize the dermonecrotic activity induced by venom in rabbits. In an effort to characterize the proteins recognized by the neutralizing monoclonal antibody, we have used different approaches as two-dimensionalelectrophoresis, neutralizing assay of hemolytic and a sphingomyelinase activities, Spot peptide synthesis, Phage display technology and immunoscreening of L. intermedia venom gland cDNA library. In an Western Blotting of L. intermedia venom 2D electrophoresis gel, the LimAb7 reacted strongly with at least 15 proteins that can belong to proteins family from dermonecrotic portion. Furthermore, LimAb7 was able to inhibit 84% and 63.5% of hemolytic and sphingomyelinase activities induced by crude venom. By phage display, all peptide mimotopes screened by LimAb7 expressed a hydrophilic portion flanked by two cysteines, these findings have suggested that this monoclonal antibody mediates their neutralizing effect by binding to conformationaldependent antigenic determinant. Two clones from L. intermedia venom gland cDNA library have identified by immunoscreening using LimAb7. The sequence analysis revealed these proteins, both wiht 283 amino acids, are isoforms with 46 and 47,5% of similarity with LiD1. The molecular weight of 32.036 and 32.180 Da and their theoricalisoelectric points are 6.36 and 5.94, respectively.